Two BRM promoter insertion polymorphisms increase the risk of early‐stage upper aerodigestive tract cancers. (12th February 2014) - Wong, Kit Man; Qiu, Xiaoping; Cheng, Dangxiao; Azad, Abul Kalam; Habbous, Steven; Palepu, Prakruthi; Mirshams, Maryam; Patel, Devalben; Chen, Zhuo; Roberts, Heidi; Knox, Jennifer; Marquez, Stephanie; et al.
Abstract Brahma (BRM) has a key function in chromatin remodeling. Two germline BRM promoter insertion–deletion polymorphisms, BRM‐741 and BRM‐1321, have been previously associated with an increased risk of lung cancer in smokers and head and neck cancer. To further evaluate their role in cancer susceptibility particularly in early disease, we conducted a preplanned case–control study to investigate the association between the BRM promoter variants and stage I/II upper aerodigestive tract (UADT) cancers (i.e., lung, esophageal, head and neck), a group of early‐stage malignancies in which molecular and genetic etiologic factors are poorly understood. The effects of various clinical factors on this association were also studied. We analyzed 562 cases of early‐stage UADT cancers and 993 matched healthy controls. The double homozygous BRM promoter variants were associated with a significantly increased risk of early stage UADT cancers (adjusted odds ratio [aOR], 2.46; 95% confidence interval [CI], 1.7–3.8). This association was observed in lung (aOR, 2.61; 95% CI, 1.5–4.9) and head and neck (aOR, 2.75; 95% CI, 1.4–5.6) cancers, but not significantly in esophageal cancer (aOR, 1.66; 95% CI, 0.7–5.8). There was a nonsignificant trend for increased risk in the heterozygotes or single homozygotes. The relationship between the BRM polymorphisms and early‐stage UADT cancers was independent of age, sex, smoking status, histology, and clinical stage. These findings suggest that the BRM promoter double insertion homozygotes may be associated with an increased risk of early‐stage UADT cancers independent of smoking status and histology, which must be further validated in other populations.